My loose tooth - Krensky, Stephen; Takahashi, Hideko (New York : Random House, 2003)
A young child describes in rhyme what it's like to have a loose tooth.
"Reading with help"--Cover.
Accelerated Reader AR
Keywords: Teeth -- Fiction; Stories in rhyme